Optimized Synthesis of a Novel 1-(trifluoroethenyl)-4-[(trifluoroethenyl)-oxy]-benzene via Palladium-Catalyzed Coupling of Arylboronic Acids with Bromotrifluoroethylene - Mahajouba, Imad Eldeen. A.; Ling, Cheng Fing (Gezira Journal of Engineering and Applied Sciences, 2016)
The synthesis of a novel 1-(trifluoroethenyl)-4-[(trifluoroethenyl)oxy]benzene at  optimized reaction conditions were described. The optimized reaction condition required only 0.25 mol% of Pd(dba) 2 and 0.5 mol% of   t- Bu 3 -P and occurred to full conversion within 12 h at 80 o C. The   novel product was assayed by 1 H and 19 F NMR spectroscopy.